Startups Unicórnio brasileiras: suas características e tecnologias utilizadas - Crisóstomo, Iandra dos Santos (BRASIL, 2022)
Technology is constantly developing, and through new business models, the world innovates at the same rate. One of these paths is through startups, which seek to undertake innovatively and add value to society. One of the apexes of startups is when they become unicorns, through the recognition of outstanding growth and success in the market in which they are inserted. This article, therefore, aims to analyze the characteristics of Brazilian unicorn startups and their leading technologies. In order to conceptualize the technologies found and their main contributions to Brazilian unicorn startups, qualitative and descriptive research was carried out, using secondary sources such as newspapers, magazines, social networks, and official government and startup websites. Thus, this work is related to 22 identified Brazilian unicorns, from which their characteristics and technologies used were compiled, so that it was possible to compare them. As some of the results of this research, the following can be mentioned: the fintech and e-commerce branches as the most prominent branches; São Paulo as the Brazilian city with the largest foundation of startups; as technologies and processes found, we can mention some such as Big Data, Cloud Computing, Artificial Intelligence, Machine Learning and Augmented Reality. Safety, greater productivity, and cost and time reductions are some of the contributions to the use of technologies observed in this study.